User Satisfaction as a Key Driver of Digital Transaction Efficiency: Kepuasan Pengguna sebagai Pendorong Utama Efisiensi Transaksi Digital - Nurholiza, Kendevani; Ajizah, Euis; Prihantono, Wahyu Hari (Indonesian Journal of Innovation Studies, 2025)
General Background: The digital revolution has transformed financial transactions, particularly through fintech innovations like QRIS, increasingly adopted by millennials and Gen Z. Specific Background: QRIS and digital finance have shown potential in enhancing transaction efficiency, yet user satisfaction remains a crucial moderating factor. Knowledge Gap: Existing studies often overlook the mediating role of user satisfaction between technological effectiveness and transaction outcomes. Aims: This study investigates the mediating effect of user satisfaction on the relationship between QRIS effectiveness, digital finance, and transaction efficiency. Results: Based on data from 210 respondents and analysis using SmartPLS 3, results show digital finance directly impacts transaction efficiency (β = 0.425, p < 0.001), while QRIS effectiveness influences efficiency only indirectly via user satisfaction (β = 0.177). Novelty: This study introduces user satisfaction as a key mediator that bridges technology performance and operational outcomes in digital payments. Implications: The findings suggest that improving UI/UX, educating users, and strengthening digital literacy can enhance the effectiveness of digital payment systems. These insights support Bank Indonesia's inclusive payment initiatives and inform fintech strategies to boost adoption and user retention.Highlight : User satisfaction significantly mediates the impact of QRIS and digital finance on transaction efficiency, highlighting its central role. QRIS effectiveness alone does not directly enhance transaction efficiency but works through enhancing user experience. Digital finance shows strong direct influence on both transaction efficiency and user satisfaction, proving its transformative potential in modern payments. Keywords : QRIS Effectiveness, Digital Finance, User Satisfaction, Transaction Efficiency, Millennials